Comparison of Performance and Risk of Tourism Companies, Restaurants and Hotels Before and During the Covid-19 Pandemic - Kinasih, Dwi Dewisri; Lawita, Nadia Fathurrahmi (Economic Education Analysis Journal, 2022)
This study aims to determine the performance and risks of tourism, restaurant and hotel companies during and before the covid 19 pandemic. This study uses four proxies to measure the company's performance, namely Return on Assets (ROA), Return on Equity (ROE), Tobins Q and Net Profit. Margin (NPM) and use two proxies to measure company risk, namely the standard deviation of Return on Assets (SDROA) and the standard deviation of Return on Equity (SDROE). The population in this study are tourism, restaurant and hotel companies for the period 2019-2020. The sampling technique used is purposive sampling technique based on certain criteria. The number of samples in this study were 15 companies with 120 observations. The data analysis technique used is to perform different tests before the pandemic and during the COVID-19 pandemic. The results showed that there were significant differences in the performance and risk of tourism, restaurant and hotel companies before the pandemic and during the pandemic.